Evaluasi Rekam Medis Elektronik dengan Metode HOT-fit di Klinik Saraf RS Mitra Plumbon - Franki Franki; Irda Sari (FORIKES, 2022)
Electronic medical records are listed in Permenkes number 269/MENKES/PER/III/2008 in article 2 which contains